Association between Physical Activity and Vitamin C Intake with HDL and LDL Levels among Overweight Students: A Cross-Sectional Study - Damayanti, Amilia Yuni; Fathimah, Fathimah; Setiyani, Ana; Sari, Fitri Komala (ARTERI : Jurnal Ilmu Kesehatan, 2025)
Obesity is a medical condition characterized by the excessive accumulation of body fat tissue. It is a significant health concern because it can lead to degenerative diseases with high morbidity and mortality rates, such as dyslipidemia. This study aimed to analyze the relationship between physical activity, vitamin C intake, and High-Density Lipoprotein (HDL) and Low-Density Lipoprotein (LDL) levels in overweight adolescents. The subjects were 50 overweight female university students aged 17-25, selected via purposive sampling. The research was conducted at UNIDA Gontor and the Widodo Medika Laboratory. Instruments used included a clinical chemistry analyzer, reagents, weight scales, and a microtoise for height measurement. A cross-sectional study design was employed, and data were analyzed using the Spearman rank correlation test. The analysis indicated no significant relationship between physical activity and HDL levels (p=0.490), nor between physical activity and LDL levels (p=0.619). In contrast, the results revealed a significant correlation between vitamin C intake and HDL levels in the overweight female students (p=0.020), with a moderate correlation strength (r=0.327). However, no significant association was found between vitamin C intake and LDL levels (p=0.744), which demonstrated a very weak correlation (r=0.047). In conclusion, this study shows a significant relationship between vitamin C intake and HDL levels in overweight female students. Conversely, no significant correlation was found with LDL levels, and physical activity did not have a significant association with either HDL or LDL cholesterol.